Порівняльний аналіз взаємопов’язаних гіпертекстових документів всесвітньої павутини та інфраструктури для підтримки електронної пошти - Ключников, Є. Ю. (ХНУРЕ, 2020)
Artificial neural networks are computing systems that simulate decision making in the biological nervous systems of animals. The biological nervous system is composed of neurons (nerve cells) connected to each other. Using the hypertext transfer protocols of the World Wide Web and the email infrastructure, it is possible to use the computing power of devices connected to the network. Using the above protocols, the calculation of the individual elements of the neural network is performed on clients (computing devices connected to the network). The regulation of the neural network operation is performed by the server